Health-related quality of life according to perceived morbidity in Chilean adolescents - Molina Cartes, Ramiro; Sepúlveda, Rodrigo; Molina, Temistocles; Martínez, Vania; González, Electra; Leal, Ingrid; George, Myriam; Montaño, Rosa; Hidalgo, Carlos (Revista Chilena de Salud Pública, 2014)
Objective. To correlate Chilean adolescents’ perceived morbidity with their Health-Related Quality of Life (HRQoL). Method. Comparative analysis of Chilean adolescents with and without perceived morbidity classified according to the International Classification of Diseases (ICD10). Information was collected through a national study, applying the KIDSCREEN-52 questionnaire, adapted culturally and validated in Chile in 2009. The ten quality life dimensions, expressed as Rasch points, were analyzed by sex, age, type of school and zones of the country. To analyze the mean differences between the variables, the Chi squared and Student’s t-test were used. The software used were STATA 10.0 and SAS 9. Results. The self perceived morbidity was assessed across the country and was more frequent in women, adolescents of younger age, students from private schools and from the north zone of the country. The lowest HRQoL Rasch points were determined in adolescents with perceived morbidity. Conclusion. The worst HRQoL in adolescents was found in those with self perceived morbidity, women, higher adolescent age, students from public schools and from the north of the country. This finding is new and a useful contribution for future national public health programs concerning adolescents.